Designing a Learning Trajectory for the Concept of Division Based on the Traditional Game of Congklak: A Design Research Study on Third Grade Students at Madrasah Ibtidaiyah - zaotul wardi (Universitas Islam Sultan Agung, 2026)
This study aims to design and analyze learning trajectories for division concepts using the traditional game congklak through a design research approach. The participants were 20 third-grade students of an Islamic elementary school. The study was conducted through three phases: preliminary design, teaching experiment, and retrospective analysis. Data were collected through classroom observations, students' learning artifacts, and pretest–posttest results to support design reflection. The findings indicate that the congklak game supported students' initial understanding of division as a fair distribution process through concrete experience. However, a retrospective analysis revealed conceptual difficulties in transitioning from concrete activities to symbolic representations, particularly with regard to the concept of remainders. The study contributes design principles for culturally based division instruction that can inform the refinement of learning designs in subsequent cycles. Keywords: design research, division, congklak